If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 73(d + -8) + -5 = 9(d + 2) + 1 Reorder the terms: 73(-8 + d) + -5 = 9(d + 2) + 1 (-8 * 73 + d * 73) + -5 = 9(d + 2) + 1 (-584 + 73d) + -5 = 9(d + 2) + 1 Reorder the terms: -584 + -5 + 73d = 9(d + 2) + 1 Combine like terms: -584 + -5 = -589 -589 + 73d = 9(d + 2) + 1 Reorder the terms: -589 + 73d = 9(2 + d) + 1 -589 + 73d = (2 * 9 + d * 9) + 1 -589 + 73d = (18 + 9d) + 1 Reorder the terms: -589 + 73d = 18 + 1 + 9d Combine like terms: 18 + 1 = 19 -589 + 73d = 19 + 9d Solving -589 + 73d = 19 + 9d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-9d' to each side of the equation. -589 + 73d + -9d = 19 + 9d + -9d Combine like terms: 73d + -9d = 64d -589 + 64d = 19 + 9d + -9d Combine like terms: 9d + -9d = 0 -589 + 64d = 19 + 0 -589 + 64d = 19 Add '589' to each side of the equation. -589 + 589 + 64d = 19 + 589 Combine like terms: -589 + 589 = 0 0 + 64d = 19 + 589 64d = 19 + 589 Combine like terms: 19 + 589 = 608 64d = 608 Divide each side by '64'. d = 9.5 Simplifying d = 9.5
| -2+14=13x-4-12x | | 2.8=2y | | 13-5x=-12 | | w-2=-3 | | 9y-8=5y+8 | | -4=g+1 | | 3(x-2)=9-2(x-5) | | 2(a+0.2)=1.6(a-4) | | 3y-4=2y-5 | | 2x^2+19x+45=0 | | -86=-9(10)+4 | | 2x^2+19+45=0 | | -4(3+t)=8 | | -58=-9(-4)+4 | | 24-35=-3x+10x-6x | | 4(3X-1)=3(5X-2)-4(2X-7) | | 18=6(q-4) | | 12-45=-4x+8x-3x | | 4x-6=2x | | 3(n-2)=-12 | | -20x-(4x-1)=15 | | 16.7=x+30.5 | | 4x-5y=10 | | -7=7(y+2) | | -6=(2y+1) | | -6+4x=5x | | 7(2W-3)-5(3W-1)=0 | | 15=3m-8m | | 5x*(6y-3)=22 | | 5+6a=41 | | -8=8(y+3) | | 23=x+25 |